Comparison of mineral spray oil, Confidor, Dursban, and Abamectin used for the control of Phyllocnistis citrella (Lepidoptera: Gracillaridae), and an evaluation of the activity of this pest in citrus orchards in northern Iran - Damavandian Mohammad Reza; Moosavi Seyedeh Fatemeh Kiaeian (Journal of Plant Protection Research, 2014)
The efficacy of three types of mineral spray oil (MSO), and Abamectin plus MSO to control the citrus leafminer Phyllocnistis citrella Stainton were compared with the conventional broad spectrum pesticides, Confidor, and Dursban, in two citrus orchards in northern Iran. Differences were found among the various concentrations of MSO in the number of mines and live larva per leaf, sampled 5 days after the application of 3 sprays at an interval of 5 days. Mineral spray oil applied at a rate of ≥ 0.65% in water, showed no significant differences when compared with Confidor, and Dursban. Abamectin plus MSO at a rate of 0.02% plus 0.50% in water respectively, provided the highest level of control and reduced the population of larva up to 85%. Generally, a concentration of ≥ 0.65% MSO in water caused a significant damage reduction. However, by reducing the MSO concentration, the rate of control was decreased. In another field experiment conducted in mature citrus orchards, the effect of two pest management types (applying just MSO vs. usage of synthetic pesticides) on the activity of P. citrella, was evaluated. The comparison results indicated that there is more P. citrella damage in orchards under pressure of synthetic pesticides than in orchards in which the synthetic pesticides were eliminated for years.